1970
DOI: 10.1063/1.1673765
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Raman and Infrared Spectra of Thiophosgene and Polymeric Species

Abstract: The Raman and infrared spectra of thiophosgene and its dimer have been reinvestigated and assignments based on new data and a normal coordinate analysis of the monomer are presented. The spectra obtained in gas, liquid, and solid phases are compared and two polymeric species and their spectra are discussed. A description of the fundamentals of thiophosgene is presented in terms of atom displacements, potential energy distributions, and Coriolis coupling coefficients. The transferability of the valence force fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In assigning these vibrational frequencies to normal modes of the ion it has been assumed that the ion retains C,, symmetry in all of the observed states. The vibrational frequencies of the groundstate molecule have been reported by Frenzel et al (9) and are compared to the observed ionic frequencies in this work.…”
Section: Thiophosgenementioning
confidence: 92%
See 2 more Smart Citations
“…In assigning these vibrational frequencies to normal modes of the ion it has been assumed that the ion retains C,, symmetry in all of the observed states. The vibrational frequencies of the groundstate molecule have been reported by Frenzel et al (9) and are compared to the observed ionic frequencies in this work.…”
Section: Thiophosgenementioning
confidence: 92%
“…2c, is there any indication of resolvable vibrational structure. The tentatively measured frequency of 260 cm-' probably corresponds to v,(a,) which has a value of 295 cm-' in the groundstate molecule (9). The integrated intensities of the three bands are approximately equal, indicating that only three orbitals are responsible, whereas four chlorine "lone pair" ionizations are excepted at these binding ener- For personal use only.…”
Section: Thiophosgenementioning
confidence: 99%
See 1 more Smart Citation
“…In the simpler case of 35 Cl 2 CS, it is a purely b-type interaction for which Frenzel et al [11] estimated the dimensionless zeta parameter to be f 4 2 b ¼À0:189, giving an interaction matrix element of about 2Bf = 0.043 cm À1 . Including this interaction in the analysis resulted in a marginally (2.5%) better fit in which (as expected) the B 0 values for m 2 and m 4 were highly correlated with the Coriolis parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous infrared studies of gas-phase thiophosgene at low and medium resolution were made by Lowell and Jones [7], Downs [8], Brand et al [9], and Hopper et al [10]. The correct assignment of the six fundamental vibrational modes in the ground electronic state was established in 1970 by Frenzel et al [11]. But as mentioned above, the overwhelming majority of spectroscopic work on this molecule has involved its electronic spectra.…”
Section: Introductionmentioning
confidence: 99%